The impact of entrepreneurship education programs (EEPs) on the entrepreneurial attitudes among higher education students in Saudi Arabia - Jaithen Alharbi; Hassan Almahdi; Aissa Mosbah (International Journal of Management, Economics and Social Sciences (IJMESS), 2018)
Using the Theory of Planned Behavior (TPB), this study aimed to investigate the impact of Entrepreneurship Education Programs (EEPs) on entrepreneurial attitudes and intentions among university students in the Kingdom of Saudi Arabia (KSA). Following the quantitative approach of enquiry, a self-administered questionnaire was distributed among two groups of students: participants studying entrepreneurship courses as part of their degrees (EEPs Group) and participants not taking any entrepreneurship course (Control Group). Data collection took place in the beginning of the semester (Pre-test/t1) and at the end of the semester (Post-test/t2). The results showed that the intention to become self-employed was positively and significantly associated to attitudes towards self-employment, subjective norms and perceived behavioral control. University students' attitudes towards self-employment, subjective norms and perceived behavioral control not only had significant and positive associations with students' intentions to become self-employed but also predicted it significantly. Therefore, while providing useful insights on the situation of entrepreneurship education, these findings help university and government planners to address unemployment of young people by creating greater entrepreneurial awareness, and jobs through entrepreneurship activities.
Keywords: D60; E27; H54; I31; 330; Entrepreneurship; Higher education; Entrepreneurship Education Programs; Entrepreneurship intention; Saudi Arabia